2016
DOI: 10.1002/2016pa002947
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical imprints of genotypic variants of Globigerina bulloides in the Arabian Sea

Abstract: Planktonic foraminifera record oceanic conditions in their shell geochemistry. Many palaeoenvironmental studies have used fossil planktonic foraminifera to constrain past seawater properties by defining species based on their shell morphology. Recent genetic studies, however, have identified ecologically distinct genotypes within traditionally recognized morphospecies, signaling potential repercussions for palaeoclimate reconstructions. Here we demonstrate how the presence of Globigerina bulloides cryptic geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 63 publications
(102 reference statements)
0
35
0
Order By: Relevance
“…This conundrum poses a challenge to the paleoceanographic researchers that unknowingly aggregate distinct G . bulloides cryptic species, particularly if they exhibit geochemical signatures like those that have been demonstrated for this species and study region (Bemis et al, ; Osborne et al, ; Sadekov et al, ).…”
Section: Resultsmentioning
confidence: 62%
“…This conundrum poses a challenge to the paleoceanographic researchers that unknowingly aggregate distinct G . bulloides cryptic species, particularly if they exhibit geochemical signatures like those that have been demonstrated for this species and study region (Bemis et al, ; Osborne et al, ; Sadekov et al, ).…”
Section: Resultsmentioning
confidence: 62%
“…bulloides model is only partially consistent with previous work. With respect to size, Friedrich et al () suggested a significant decrease in Mg/Ca of ~0.2 mmol/mol per 100 microns with increasing shell size, while Elderfield et al () found a similar magnitude of change but of opposite sign, and others found no relationship with size (Martínez‐Botí et al, ; Sadekov et al, ). With respect to shallow carbonate parameters, culture studies suggest that G .…”
Section: Discussionmentioning
confidence: 99%
“…Error propagation (Mohtadi et al, 2014) yields an average propagating 1σ error of 0.89 • C. We are aware of a potential bias introduced by a genotype-specific fractionation of Mg / Ca ratios, which was recently shown to occur between two species of G. bulloides that prefer warm water (type I) and cool water (type II) in the Arabian Sea WA-PLS = weighted-averaging partial-least-squares method. (Sadekov et al, 2016). However, the high numbers of G. bulloides observed throughout the studied interval of core SL163 suggest intense upwelling conditions and we therefore assume that we mainly sampled specimens of the coolwater genotype, type IIf, which is restricted to upwelling stations of the northern Oman margin (Sadekov et al, 2016).…”
Section: Pf Faunal Analyses Of Core Sl163 and Palaeothermometrymentioning
confidence: 99%
“…(Sadekov et al, 2016). However, the high numbers of G. bulloides observed throughout the studied interval of core SL163 suggest intense upwelling conditions and we therefore assume that we mainly sampled specimens of the coolwater genotype, type IIf, which is restricted to upwelling stations of the northern Oman margin (Sadekov et al, 2016).…”
Section: Pf Faunal Analyses Of Core Sl163 and Palaeothermometrymentioning
confidence: 99%
See 1 more Smart Citation